Effects of Rational Emotive Behaviour Therapy and Emotional Intelligence on Mathematics Anxiety of In-School Adolescents in Owerri Municipal Nigeria - Okoiye, Ojaga Emmanuel; Ukah, Petronilla Ngozi; Nwoga, Anayochi N. (European Journal of Sustainable Development, 2013)
The impact of mathematics anxiety on the academic well-being of most in-schooladolescents is quite frustrating. This development causes fear, apprehension and learnedhelplessness that can mar in-school adolescent’s potentials. Therefore, in line with thiscontext, this study through a pretest-posttest, control group quasi-experimental designinvestigated the effects of rational emotive behaviour therapy and emotional intelligencetechnique on the mathematics anxiety of in-school adolescents in Owerri Municipal ImoState Nigeria. Purposive sampling technique was used to select 60 participants from threerandomly selected secondary schools in Owerri Municipal. The participants were randomlyassigned to treatment and control groups. The two treatment groups were exposed toeight-weeks training in Rational Emotive Behaviour Therapy and Emotional Intelligence,while participants in the control group received no training. One validated instrument:Fennema-Sherman Mathematics Anxiety Scale (FSMAS) (?= 0.92) was used. Fourhypotheses were tested at 0.05 level of significance. Data was analysed using Analysis ofCovariance. There was significant main effect of treatment on the ability of in-schooladolescents to manage mathematics anxiety (F (3, 56) = 26.98, p<0.05). Also, age wasfound to have significant main effect on the mathematics anxiety of in-school adolescentsparticipants (F (2, 57) = 4.287, p<0.05). The results further indicated that there was nosignificant main effect of gender on the mathematics anxiety of in-school adolescentsbetween male and female participants. Likewise, there was no significant interaction effectof treatment, age and gender on mathematics anxiety of in-school adolescent’sparticipants. School counselling psychologists could adopt the two interventions tomanage mathematics anxiety of in-school adolescents.